2017
DOI: 10.18535/jmscr/v5i2.80
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of CSOM Unsafe Type in Rural Population of Central India

Abstract: Background: Chronic suppurative otitis media (CSOM) presents with a typical history of recurrent otorrhea with tympanic membrane perforation. High resolution computed tomography (HRCT) of temporal bone is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…Our study also showed that the young active age group (11-30 years old) was the most affected (73%). Similar results can be seen in studies conducted by Agrawal et al 12 and Jamro et al 14 The main reason for this age group being affected by this disease may be the fact that this is the most active and healthconscious age group.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study also showed that the young active age group (11-30 years old) was the most affected (73%). Similar results can be seen in studies conducted by Agrawal et al 12 and Jamro et al 14 The main reason for this age group being affected by this disease may be the fact that this is the most active and healthconscious age group.…”
Section: Discussionsupporting
confidence: 89%
“…This maledominance model is prevalent throughout the world. 9,11 However, studies by Agrawal et al 12 and Balasubramanian et al 13 reveal a pattern of female predominance. Our study also showed that the young active age group (11-30 years old) was the most affected (73%).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation